1994
DOI: 10.1200/jco.1994.12.6.1137
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant CYVADIC chemotherapy for adult soft tissue sarcoma--reduced local recurrence but no improvement in survival: a study of the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group.

Abstract: Adjuvant chemotherapy with CYVADIC cannot be recommended outside the context of a clinical trial. Experience from this study has been used to plan a trial of neoadjuvant chemotherapy with doxorubicin/ifosfamide, which is currently in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(91 citation statements)
references
References 24 publications
7
79
0
5
Order By: Relevance
“…A response rate of 45% and a 5-year overall survival rate of 66% for patients with Stage III disease was reported [24]. In one European trial, adjuvant chemotherapy in the form of cyclophosphamide, vincristine, doxorubicin, and dacarbazine (CYVADIC) reduced local recurrence but not overall survival, similar to our study [4]. One theory regarding how chemotherapy might affect local control is that chemotherapy may affect actively dividing cells at the margins of tumors [19].…”
Section: Discussionsupporting
confidence: 85%
“…A response rate of 45% and a 5-year overall survival rate of 66% for patients with Stage III disease was reported [24]. In one European trial, adjuvant chemotherapy in the form of cyclophosphamide, vincristine, doxorubicin, and dacarbazine (CYVADIC) reduced local recurrence but not overall survival, similar to our study [4]. One theory regarding how chemotherapy might affect local control is that chemotherapy may affect actively dividing cells at the margins of tumors [19].…”
Section: Discussionsupporting
confidence: 85%
“…The regimens that were applied are listed in Table 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] High-dose chemotherapy (HDC) with hematopoietic stem cell rescue was received by 51 patients, including 48 patients who received autologous peripheral blood stem cell transfusion (PBSCT) and 3 patients who underwent autologous bone marrow transplantation.…”
Section: Treatmentmentioning
confidence: 99%
“…If the tumor is unresectable, neoadjuvant therapies (radiotherapy, chemoradiation, chemotherapy) are recommended primarily, even if some authors have not found any improvement in overall survival. 8 Tumors that become resectable after preoperative treatment can be treated with surgery. Otherwise, definitive radiotherapy is recommended.…”
Section: Discussionmentioning
confidence: 99%